A case study of long gravity wave crests in noctilucent clouds and their origin in the upper tropospheric jet stream. Issue 23 (10th December 2016) - Dalin, P.; Gavrilov, N.; Pertsev, N.; Perminov, V.; Pogoreltsev, A.; Shevchuk, N.; Dubietis, A.; Völger, P.; Zalcik, M.; Ling, A.; Kulikov, S.; Zadorozhny, A.; et al.
Abstract: Atmospheric gravity waves with very long crests (of 450–500 km length) and short horizontal wavelengths of about 20 km were observed in noctilucent clouds and were studied in detail for the first time. The gravity waves were slowly moving in opposite direction to the background wind indicating their forced generation outside the mesopause region. A ray‐tracing analysis using meteorological reanalysis and empirical atmospheric model data shows that a source of such peculiar gravity waves observed in noctilucent clouds was located near the tropopause and could be associated with the jet stream at altitudes 8–10 km. Two considered examples of very long wave crests confirm a significant role of the upper tropospheric jet stream as a source of gravity waves and reveal that these waves could propagate without critical levels to the mesopause in summertime. Key Points: First observation and analysis of very long wave crests (450‐500 km length) were carried out in NLC A ray‐tracing analysis suggests a possible source of observed waves located in the upper tropospheric jet stream Gravity waves could propagate from the tropopause to the mesopause without reaching critical levels